2018
DOI: 10.1080/21691401.2018.1452750
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles Clinacanthus Nutans leaves extract induced apoptosis towards oral squamous cell carcinoma cell lines

Abstract: AgNps-CN have shown potential in inhibiting HSC-4 cell lines. IC was low compared to few studies involving biosynthesized of silver nanoparticles. Apoptosis effects were shown towards HSC-4 cell lines by the increased in Bax/Bcl-2 protein ratio. Further study such as PCR or in vivo studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…This indicated that the AgNPs become more potent after reduction of silver ions by the extracts utilized, showing high mortality rate (45%) when applied to HeLa cells ( Figure 7(B,Cviii)). Our findings are in line with the previous studies, suggesting potential use of metallic NPs against cancer cells [38][39][40].…”
Section: Anticancer Activity Using Hela Cell Linesupporting
confidence: 93%
“…This indicated that the AgNPs become more potent after reduction of silver ions by the extracts utilized, showing high mortality rate (45%) when applied to HeLa cells ( Figure 7(B,Cviii)). Our findings are in line with the previous studies, suggesting potential use of metallic NPs against cancer cells [38][39][40].…”
Section: Anticancer Activity Using Hela Cell Linesupporting
confidence: 93%
“…Identifying the size and morphology of the plant-mediated syntheses of metallic nanoparticles is important because it will allow for the engineering of nanoparticles with proper shapes and sizes for the maximal accumulation in a malignant tumour. Although nanoparticle size and morphology have significant effects on cytotoxicity potency, other parameters are important as well, such as surface properties, aggregation/agglomeration state, solubility, and surface properties; attached functional groups, surface area, and surface charges also play important roles in influencing the resultant pharmacokinetics and pharmacodynamics of nanoparticles [ 22 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were centrifuged (Heraeus Megafuge 16 centrifuge, Thermo Scientific) at 1000 rpm for 5 min, and the supernatant was aspirated. Lastly, 5 mL of fresh warm medium was added and pipetted up and down with the pellet, then 50 µL of the cells were added to 50 µL of trypan blue to calculate the cell using hemocytometer (Yakop et al, 2018).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%